PENGARUH RASIO KEUANGAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI TAHUN 2014 – 2017 - Kusumaningtyas, Febriana; Rachmawati Dewi, Riana; Samrotun, Yuli Chomsatu (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
Corporate1dividend policy is policy taken by1the company in an effort to achive a balance between dividends and company growth in the future. This study analyzes the effect of the retrun on asset and growth on devidend payout ratio in consumer goods industry companies listed on the Indonesia stock exchange in 2014 - 2017. Sampling was done by purposive sampling, so that a sample of 9 companies was obtained. The results showed that the variable retrun on asset positively towards devidend payout ratio, current ratio and debt to equity ratio had no effect on devidend payout ratio, while variable growth negatively affected devidend payout ratio.